A Survey on Various Issues Big Data in Cloud Computing - Jain, Gaurav; Gupta, Kunal; Kushwah, Arpit; Agrawal, Abhishek (International Journal of Computer Sciences and Engineering, 2025)
Big data is a key concept that cannot be over looked in the IT world considering the prominent increase in data, and data related services, it is important to explore this field and look at ways to improve data service delivery especially in the cloud. (CC) on the other hand helps in tackling the issue of storage and data service. This research focus on the two key concept big data and (CC) and some of the issues and challenges that are inherent with the deployment of cloud services and big data. The shows study that security challenges are among the most prominent issue in the cloud and big data services. The plumbing issue and some other issues such as the issue of the cost to run cloud services in handling big data were observed. Also the issues of service level agreement which gives an organization the assurance of enjoying all services rendered by the organization running the cloud services. After considering some of the issues associated with big data and (CC), some solution was suggested towards improving the two key concepts which will go a long way in increasing the adoption rate of (CC) by organizations. It is important for organizations to consider the nature of how their data will grow in the future before deploying any cloud service in their business.